(untitled) (Castilla. Estudios de Literatura, 2018)
In the context of the nineteenth-century imperialist biopolitics, the war in Cuba and the Philippines questioned the Spain’s racial vigor and implied a rethinking of its national configuration. Emilia Pardo Bazán actively participated in this debate during the conflict and after the defeat of 1898. This article analyzes the elaboration of Spain’s image through the representation of the colonies in the short stories that she published in newspapers from 1896 to 1899. The study of the colonial literary space reveals the transformation that the idea of the Spanish nation underwent from a united and inclusive homeland, constituted by a civilizing metropolis and its colonies, to a degenerated nation that succumbed to savagery. Pardo Bazan’s stories belong to a literature emerged from the war that, although not abundant or canonical, should not be omitted for its wide dissemination and its influence on national construction.